Desmoplakin and features of desmoplakin cardiomyopathy - R. P. Myasnikov; N. N. Kuzina; D. A. Nefedova; A. V. Kiseleva; O. V. Kulikova; A. N. Meshkov; M. M. Kudryavtseva; E. A. Mershina; M. g. Divashuk; E. V. Ryzhkova; M. S. Kharlap; O. M. Drapkina (Российский кардиологический журнал, 2023)
Inherited cardiomyopathies (CMP) are a group of heterogeneous diseases characterized by myocardial disorders that is not caused by coronary artery disease, hypertension, valvular and congenital defects. With the development of imaging methods and molecular genetic diagnostics, it has become clear that many CMPs are characterized by phenotypic and genotypic "crossover". And although the genetic component does not always determine the specific phenotype of the disease, genetic testing plays a significant role in risk stratification, determining the prognosis and management of patients, as well as conducting family screening. Considering the high diagnostic and prognostic value of genotype, novel genotype-based strategies for classifying CMP have been proposed in recent years. One example of such a genotype-specific approach is the identification of desmoplakin CMP as a separate independent clinical entity. The article presents a case of a family with a pathogenic DSP gene variant (p.Gln948LysfsTer29) identified in three generations, leading to the development of a specific CMP phenotype. A comprehensive examination was carried out. We demonstrated the stages of natural disease course, as well as management strategy for patients with desmoplakin CMP were proposed.